UKRI Open Access Policy Consultation Imperial College London Response - Banks,C (Imperial College London, 2020)
This document summarises the Imperial College London response to UKRI’s Open Access Review consultation: https://www.ukri.org/funding/information-for-award-holders/open-access/open-access-review/ In addition to signposting the full UKRI consultation documentation and list of questions, consultation on the Imperial College response to the UKRI OA review has been undertaken as follows· Presentation and discussion at the Vice Provost’s Advisory Group for Research· Presentations at each of the four Faculty Research Committee meetings· Via a recorded online presentation accompanied by a short questionnaire· Through information circulated via faculty and departmental mailing lists· Via social media including Twitter, and YammerResponses to multiple choice questions are highlightedThe response was submitted by Chris Banks, Assistant Provost (Space) & Director of Library Services on behalf of the College.